2018
DOI: 10.1016/j.exger.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 activator diminazene aceturate reduces adiposity but preserves lean mass in young and old rats

Abstract: The obesity epidemic is multi-generational and is particularly debilitating in the aging population, necessitating the use of pharmaceutical interventions. Recent evidence suggests that increasing the activity of the angiotensin converting enzyme-2 [ACE2]/angiotensin-(1-7)[Ang-(1-7)]/Mas receptor (MasR) axis in obese animal models leads to significant reductions in body weight. It was hypothesized that activation of ACE2 via diminazene aceturate (DIZE) will significantly reduce body weight of rats fed a high f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
3
10
0
Order By: Relevance
“…All other mice received equivalent volumes of vehicle (saline) injections. This dose was based on several previous studies showing that the optimal dose of DIZE in inducing ACE2 activity was 15 mg/kg/ day [39,43,44] and a preliminary study of our own across a range of DIZE concentrations by IP that confirmed previous findings (data not shown).…”
Section: Drugssupporting
confidence: 70%
“…All other mice received equivalent volumes of vehicle (saline) injections. This dose was based on several previous studies showing that the optimal dose of DIZE in inducing ACE2 activity was 15 mg/kg/ day [39,43,44] and a preliminary study of our own across a range of DIZE concentrations by IP that confirmed previous findings (data not shown).…”
Section: Drugssupporting
confidence: 70%
“…Second, endothelial dysfunction with aging was augmented in the ACE2-deficient mice [ 32 ]. Third, administration of an Ang 1-7 analogue was associated with improved aging-related neuroinflammation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diminazene aceturate (DIZE) is a potent ACE2 activator and has been shown to exert beneficial effects in experimental models of cardiovascular diseases [142]. Bruce et al reported that DIZE reduced adiposity but preserved lean mass with increased serum ACE2 activity in young and old rats [143]. Accumulating evidence suggests that exercise is a promising non-pharmacological intervention to modulate the RAS [144,145].…”
Section: Pharmacological or Non-pharmacological Modulation Of Ace2 Inmentioning
confidence: 99%